The role of innovation and customer service in the success of Malaysian F&B SME - Yusuf, Yusni Munirah; Ab Rahman, Siti Maziah; Bustaman, Hasnun Anip (Journal of Islamic, Social, Economics and Development, 2025)
This paper represents a conceptual framework that explores the relationship between innovation and customer service in the Malaysia’s food and beverages industry. In rapidly changing environment and the increasing Gen z population, the F&B sector facing the increasing pressure from the external force which could constraints the business from growing. This study synthesizes existing literature on innovation types which is on the product and services approach that a business could apply to gain desired business success. By offering a structural approach to understanding how innovation and customer services influences business success, this conceptual framework serves as foundation for both academic research and practical implications.